Quantitative Structure Activity Relationship Studies and Molecular Dynamics Simulations of 2-(Aryloxyacetyl)cyclohexane-1,3-Diones Derivatives as 4-Hydroxyphenylpyruvate Dioxygenase Inhibitors - Fu, Ying; Liu, Yong-Xuan; Yi, Ke-Han; Li, Ming-Qiang; Li, Jia-Zhong; Ye, Fei (Frontiers in Chemistry, 2019)
4-Hydroxyphenylpyruvate dioxygenase (HPPD) is a significant enzyme in the biosynthesis of plastoquinone and tocopherol, moreover, it is also potential target to develop new herbicide. The computer-aided drug design (CADD) was employed to the efficient discovery of new HPPD inhibitors in this study. Forty-three compounds with known activities were used to generate CoMFA and CoMSIA models based on common framework and molecular docking. The structural contribution to the activity was determined which provided further information for the design of novel inhibitors. Molecular docking was used to explain the changes in activity caused by the binding mode between ligand and protein. The molecular dynamics (MD) results indicated that the electrostatic energy was the major driving force for ligand-protein interaction and the Phe403 made the greatest contribution to the binding. The present work provided useful information for the rational design of novel HPPD inhibitors with improved activity.